PENGARUH MULTILITERASI TERHADAP PERKEMBANGAN MINAT MENULIS DI KALANGAN MAHASISWA - Wahyudin, Dikdik (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The ability of writing skills as something important for someone, especially for people who are in the world of education. They should be skilled in writing skills, but the reality in the field is very different. There are still many students who take the Indonesian language and literature education study program who have not mastered writing skills. The formulation of the problem in this study is how the effect of the multiliteration learning model on the development of student writing? Based on the formulation of the problem, the aim of this study is to determine the effect of multiliteration on the writing development of Indonesian language and literature education students at the IKIP Siliwangi. The research instrument used using a questionnaire or questionnaire with a research sample of 10 people. The research method used a qualitative descriptive method. Thus the results of research on the effect of multiliteracy on the development of student writing show that 60% of students are interested in writing poetry, 30% of short stories, and 10% of novels. Thus the influence of this multiliterative learning model is very influential on the development of writing among students.